Level of resilience in non-practicing and practicing physical exercise in elderly Nível de resiliência em idosas praticantes e não praticantes de exercício físico - Mazo G.Z.* (2016)
© 2016 Edições Desafio Singular.The aim of this study was to analyze the level of resilience of older practitioners (GP) and non-exercising (GNP) as their sociodemographic characteristics, health conditions and stressful events. The study included 164 elderlies, being 85 GP and 79 GNP. We used a diagnostic plug to collect sociodemographic data, health conditions, the Inventory of Stressful Events and Resilience Scale. We used the descriptive and inferential statistics. No significant difference in the level of resilience between the groups (p= 0.404). The old GP with higher education had higher resilience and lower intensity of stressful events. In both groups, the highest level of resilience was associated with lower intensity of stressful events. The level of resilience is not related to physical exercise, but older women who regularly exercise and have a higher level of resilience have lower intensity of stressful events.